2022
DOI: 10.3390/nano12224008
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Adsorption Performance Study of Graphene Quantum Dots@ZIF-8 Composites for Highly Efficient Removal of Volatile Organic Compounds

Abstract: Based on the large specific surface area and excellent adsorption potential of graphene quantum dots (GQDs) and zeolitic imidazolate framework-8 (ZIF-8) materials, a GQDs@ZIF-8 composite was constructed to achieve optimal matching of the microstructure and to acquire efficient adsorption of volatile organic compounds (VOCs). GQDs and ZIF-8 were synthesized and then compounded by the solution co-deposition method to obtain GQDs@ZIF-8 composites. GQDs were uniformly decorated on the surface of the ZIF-8 metal–or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Another important outcome of this investigation is that, in almost all studies, the constant k 1 is greater than k 2 . Nyankson et al [97] showed that the uptake of MB using zeolite/cerium oxide occurs in three steps, and they obtained a three-step mechanism.…”
Section: Sorption Kineticsmentioning
confidence: 99%
“…Another important outcome of this investigation is that, in almost all studies, the constant k 1 is greater than k 2 . Nyankson et al [97] showed that the uptake of MB using zeolite/cerium oxide occurs in three steps, and they obtained a three-step mechanism.…”
Section: Sorption Kineticsmentioning
confidence: 99%